3D Finite Element Model for Shear-dominant Failure of Reinforced Concrete Beams - Ridwan Rahman; Ilham Akbar; Rofriantona Rofriantona (AMTS and Faculty of Engineering - Universitas Riau, 2021)
This study explores the 3D FE modelling approach in determining the behaviour of shear-dominant responses of RC beams. Five RC beams (A1, A2, B1, C2 and C3) with different cross-sections, amount of tension reinforcement area, amount of shear reinforcement and the length of the span was analysed and the results were compared with the results of the experiment and 2D analysis available in published literature. RC beams analysed in this FE study were constructed as a discrete model using ABAQUS software. The concrete and the plate for loading as well as for supports were modelled using the C3D8R element while longitudinal steel bars and stirrups were modelled with the T3D2 element. The interaction between the steel bar and the concrete in the FE model was assumed perfectly bond. The material behaviour of concrete was modelled with the damage plasticity model where the yield or failure of the material was governed by the tensile cracking and the compressive crushing of the concrete by introducing the hardening variables. The results showed that crack propagation in the FE analysis matched the cracks observed in the test. The crack pattern on Beam A1, A2, B1 and C2 indicated that the specimens experienced flexure and shear failure while Beam C3 experienced less brittle behaviour. Estimates of strength and the load–deformation response of 3D analysis were certainly achieved with reasonable accuracy compared to that of 2D analysis. The difference of experiment-to-2D strength (Pu,exp - Pu,2D / Pu,exp) had a mean of 4.53 whereas the difference of experiment-to-3D strength (Pu,exp - Pu,3D / Pu,exp) had a mean of 1.83. Furthermore, the displacements at ultimate load gained in the 3D analysis were comparable to those of experiments. The difference of experiment-to-2D (du,exp - du,2D / du,exp) and experiment-to-3D (du,exp - du,3D / du,exp) midspan displacement had a mean of 19.91 and 10.89, respectively.